Protective Efficacy Evaluation of NPt-NPt-VP1₁₋₁₀₀Protein as a Candidate Vaccine Against Enterovirus 71 Infections in Mouse Model - Ch'ng, Wei Choong (2010)
Enterovirus 71 (EV71) is a type of human virus belonging to the Enterovirus genus within the Picornaviridae family. The virus mainly causes hand, foot and mouth disease in children which sometimes lead to severe neurological complications. Outbreaks of EV71 infections are serious health threats since effective antiviral drugs or vaccines are not currently available. Therefore, development of an effective vaccine is ideal for the prevention and control of EV71 disease outbreak. The use of recombinant EV71 viral protein offers an alternative to the more risky method of using whole live attenuated or inactivated virus. Our previous study using truncated VP1 protein (VP11-100) of EV71 virus fused to a carrier protein showed strong immune response in adult rabbits. The study however, did not address the issue of its effectiveness in young animals. This factor is important since EV71 mostly infected children younger than 5 year-old. In the present study, we investigated the protectiveefficacy of NPt-VP11-100 protein against EV71 infection in a recently-developed newborn mouse model system. Prior to investigation in the newborn mouse model, we evaluated the type of immune responses developed by adult mice against NPt-VP11-100 protein. In adult mice, the protein induced high levels of anti-VP1 IgG production. Purified VP1 antigen stimulated activation, proliferation and differentiation of splenocytes harvested from the immunized mice. They also produced high levels of IFN-γ. Following determination of immune responses towards NPt-VP11-100 protein in adult mice, we performed immunization and virus challenge study in newborn mice model. Since the mice was only susceptible to EV71 infection before they are 14 day-old, only two doses of immunization were carried out. Even though the IgG produced lacked neutralization properties, immunized newborn mice were still partially protected from EV71 viral challenge. They showed high (47.4%) survival rate as compared to the control group and importantly, 50% of them fully recovered from paralysis symptoms at the end of the study. Histological analysis of all the surviving mice revealed a complete clearance of EV71 viral antigens from their brains and spinal cords. In hind limb muscles, the level of antigens detected correlated directly with tissue damage and their paralysis symptoms. We also initiated a similar study in a hamster model which had longer EV71 susceptibility period. In hamster, the NPt-VP11-100 protein was also found to be highly immunogenic. Findings from the study showed that immunization with NPt-VP11-100 protein in newborn mice model confer them a partial protection against EV71 infection. NPt-VP11-100 protein therefore offers a great promise towards finding a vaccine for EV71 infections.